3D characteristics of pores in SiC particle preforms with different starch contents by X-ray micro-computed tomography. Issue 18 (15th December 2019) - Xie, Bin; Zhao, Haidong; Long, Han; Peng, Jialin; Liu, Ruizhe
Abstract: High resolution X-ray micro-computed tomography was used to non-destructively characterize pore structures in silicon-carbide particle (SiCp) preforms with different starch contents. Three-dimensional models for porosity network were reconstructed, and characteristics for both pores and throats were calculated for the preforms. As the starch contents increased (no more than 8 wt%), the pores with small size and the "pore-neck" structures were formed due to the gap expansion caused by the escape of decomposed gas of starches. When using 15 wt% starches, larger gap expansion due to decomposed gas led to the connection of neighbored small pores and the break of "pore-neck" structures, and hence, increased the pore and throat sizes, pore coordination numbers and connectivity. The porosity measured by the Archemedes', mercury porosimetry, and 3D X-ray μ-CT methods were compared and discussed. It was found that the mercury porosimetry method may underestimate pore fractions and sizes.